2018
DOI: 10.1111/codi.14267
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic technique of modified extraperitoneal (retrotransversalis) end colostomy for abdominoperineal excision

Abstract: This single-institution retrospective case series demonstrates that laparoscopic extraperitoneal retrotransversalis end colostomy is feasible, safe and effective in preventing parastomal hernias and stomal prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Herein, we present the technique for constructing an EPC during laparoscopic APR applied in our clinic, similar to techniques reported by other authors (6,7). Usually, the colostomy site coincides with the assistant trocar, located through (6) or lateral to the lateral border (7) of the left rectus abdominis muscle at or slightly above the level of the umbilicus.…”
Section: Methodsmentioning
confidence: 71%
See 2 more Smart Citations
“…Herein, we present the technique for constructing an EPC during laparoscopic APR applied in our clinic, similar to techniques reported by other authors (6,7). Usually, the colostomy site coincides with the assistant trocar, located through (6) or lateral to the lateral border (7) of the left rectus abdominis muscle at or slightly above the level of the umbilicus.…”
Section: Methodsmentioning
confidence: 71%
“…Herein, we present the technique for constructing an EPC during laparoscopic APR applied in our clinic, similar to techniques reported by other authors (6,7). Usually, the colostomy site coincides with the assistant trocar, located through (6) or lateral to the lateral border (7) of the left rectus abdominis muscle at or slightly above the level of the umbilicus. During the abdominal phase of the operation when the rectum is fully mobilized, the descending colon is resected at an adequate level to provide sufficient length of the colon, thus facilitating the construction of a tension-free end colostomy at the assistant tro-…”
Section: Methodsmentioning
confidence: 71%
See 1 more Smart Citation
“…Definitive fixation of the rectum is postulated to occur with the mesh in the early post-operative phase, and then being driven by posterior fibrosis in the midto late phases. Using a resorbable (biological) mesh may protect the patients from erosions caused by non-resorbable meshes observed with the Ripstein and Orr-Loygue procedures [11,12].…”
Section: Robotic Mesh Rectopexy For Rectal Prolapse: the Geneva Techn...mentioning
confidence: 99%
“…Extraperitoneal tunneling of an end colostomy has been proposed as a technique to decrease the risk of PSH. [113][114][115][116] In a meta-analysis of 10 studies (2 RCTs and 8 retrospective studies) including 347 patients with an extraperitoneal colostomy and 701 patients with a conventional colostomy, Kroese et al 117 reported that extraperitoneal tunneling was associated with significantly lower PSH rates (6.3% versus 17.8%; p < 0.001) and significantly lower stoma prolapse rates (1.1% versus 7.3%; p = 0.01). In this study, there was no difference in complication rates between the groups.…”
Section: Extraperitoneal Tunneling Of An End Colostomy May Decrease T...mentioning
confidence: 99%